The potential of sovereign sustainability-linked bonds in the drive for net-zero - Alexander Lehmann; Catarina Martins (Bruegel, 2023)
European Union governments have for some years issued green bonds that raise funds for climate-related spending. These bonds have been received well in capital markets but because they promise a certain use of proceeds, they complicate budget management and may not match investors' claims of having an impact on national climate policies. Public commitments made by major investors and asset owners suggest that limiting climate transition risks and the assessment of the alignment of sovereigns with net-zero targets will now become key determinants of portfolio allocation. Yield differentials in bond markets are already beginning to reflect transition risks that arise from the inadequate pursuit by issuers of climate targets. Unlike standard green bonds, sustainability-linked bonds (SLBs) create a link between performance (outcome) indicators and the financial terms of the bonds. SLBs have grown rapidly in importance in private markets and are now being assessed by sovereign issuers. We show that sovereign SLBs could help incentivise climate policies in EU countries, and accelerate emission reductions. They would be an effective tool for signalling commitment. A common EU framework for issuance by EU countries would enhance capital market integration and the transparency of national policies, and would limit climate transition risks in EU capital markets more broadly.
Keywords: 330